Caries Experience among Children with History of Neonatal Stunting - Yohana, Siska; Indriyanti, Ratna; Suryanti, Netty; Rahayuwati, Laili; Juniarti, Neti; Setiawan, Arlette S. (European Journal of Dentistry, 2022)
Objective Children with neonatal growth retardation (defined as birth length <48cm) are at risk for chronic malnutrition that begins before birth and continues into infancy. Stunting can adversely affect a child's growth and development, including oral health itself, and especially the experience of dental caries. This study analyzed the dental caries experience in children with neonatal growth retardation.Materialsand Methods This was a baseline and 1-year follow-up analysis of a cohort of stunted children in a potential stunting site in Bandung City. Annual data collection included interviews with mothers and dental and anthropometric examinations of children. Descriptive analysis was performed in SPSS.Statistical Analysis Data were recorded on paper forms and manually entered into a Microsoft Excel spreadsheet for later analysis using IBM SPSS (version 23.0). After assessment, descriptive statistics was generated prior to bivariate analysis.Results Fifty-five children met the inclusion criteria and participated in the 1-year study. Decay, missing, filling teeth (Dmft) was in the intermediate category (4.13) at baseline and fell into the high category (5.16) at 1-year follow-up, although the increase in caries remained in the low category.Conclusion Dysplastic children with a history of neonatal developmental delay experience dental caries beginning in the first year of life and may become more severe later in life.
Keywords: neonatal stunting; malnutrition; dental caries; dental caries index